2018
DOI: 10.3390/toxins10070276
|View full text |Cite
|
Sign up to set email alerts
|

Low Levels of Chito-Oligosaccharides Are Not Effective in Reducing Deoxynivalenol Toxicity in Swine Jejunal Explants

Abstract: Deoxynivalenol (DON) is a mycotoxin that affects the intestinal morphology of animals, impairing nutrient intake and growth. On the other hand, dietary supplementation with functional oligosaccharides as chito-oligosaccharides (COS) has shown positive effects on the intestinal health of piglets. Therefore, the objective of the present study was to evaluate the effect of low doses of COS in preventing DON-induced intestinal histological changes, using a swine jejunal explant technique. The intestinal explants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…The addition of DON can lead to several histological changes at moderate to severe level, such as apical necrosis and villous atrophy and fusion. Meanwhile, DON can reduce the villi height, crypt depth, and goblet cell density significantly [35]. This study analyzed the morphological integrity in intestinal tissue of weaning rabbits induced by DON.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of DON can lead to several histological changes at moderate to severe level, such as apical necrosis and villous atrophy and fusion. Meanwhile, DON can reduce the villi height, crypt depth, and goblet cell density significantly [35]. This study analyzed the morphological integrity in intestinal tissue of weaning rabbits induced by DON.…”
Section: Discussionmentioning
confidence: 99%
“…These include short-term preservation during culture and careful and laborious preparation [ 39 , 61 ]. While these limitations are technical in nature, ex vivo intestinal models are widely used to evaluate gastrointestinal toxicity induced by mycotoxins [ 68 , 69 , 70 , 71 , 72 ].…”
Section: Experimental Models Used To Assess the Intestinal Barriermentioning
confidence: 99%
“…However, methods to remove T-2 toxin from feed and food can be unstable and expensive and can further affect grain quality [15]. Physical adsorption is more effective and directly detoxifies mycotoxins by inhibiting absorption in the gastrointestinal tract [16], but there is a lack of efficient adsorbent for T-2 toxin and deoxynivalenol (DON) [17]. Previous studies have reported that adsorbents contain aluminosilicates, such as bentonite [18], montmorillonite [19], and zeolite [20], displaying an ability to effectively protect against zearalenone [21], aflatoxin B 1 (AFB 1 ), and fumonisin B 1 (FB 1 ) [22] in several farm and experimental animals.…”
Section: Introductionmentioning
confidence: 99%